VEHIQL-AI: An Intelligent Automotive Marketplace Integrating Visual Vehicle Recognition and AI-Powered Calling Agent Assistance (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research introduces an AI-driven automotive marketplace platform designed to enhance the vehicle buying and selling ecosystem through intelligent automation and data-driven decision-making. The system enables image-based vehicle search using computer vision models capable of extracting vehicle attributes such as make, model, variant, and features directly from user-uploaded images. The platform integrates an AI-powered conversational calling agent that analyzes customer intent, budget, and usage patterns to provide personalized vehicle recommendations and automated test drive booking.Experimental evaluation demonstrates that the proposed system achieves 93.4% vehicle recognition accuracy, an R² score of 0.87 for price prediction, and an average recommendation response time below 2.1 seconds, improving decision-making efficiency compared to traditional automotive marketplace platforms.